Real-Time Visualization of Scent Accumulation Reveals the Frequency of Floral Scent Emissions - Kim, Hyoungsoo; Lee, Gilgu; Song, Junyong; Kim, Sang-Gyu (Frontiers in Plant Science, 2022)
Flowers emit a bouquet of volatiles to attract pollinators or to protect flowers from pathogen and herbivore attacks. Most floral volatiles are synthesized in the cytoplasm of petals and released into the headspace at a specific time of day. Various floral scent sampling methods coupled with gas chromatography-mass spectrometry have been used to measure the quality and quantity of floral volatiles. However, little is known about the emission patterns of floral scents. In most cases, it is still unclear whether floral scents emit continuously or discontinuously. Here we measured the frequency with which lily flowers emit scents using optical interferometry. By analyzing the refractive index difference between volatile organic compounds and ambient air, we were able to visualize the accumulation of the volatile vapors. The frequency of volatile emission was calculated from the unique footprint of temporal power spectrum maps. Based on these real-time measurements, we found that lily flowers emit the volatile compounds discontinuously, with pulses observed around every 10-50 min.